ACHIEVEMENT STRATEGY OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) IN MOROWALI UTARA - Sereh, Jeane Lelyana; Randa, Fransiskus; Daromes, Fransiskus E. (Accounting Profession Journal (APAJI), 2025)
This research aims to analyze strategies and implementation for achieving the Sustainable Development Goals (Sustainable Development Goals) of North Morowali Regency as one of the newly developing areas with the entry of the nickel mining industry. Using qualitative, interpretive research methods and a phenomenological approach, the results of the research show that the regional government of North Morowali Regency has implemented a number of programs as a strategy for achieving the Sustainable Development Goals, which can be said to be very good, but overall only 8 indicators have been identified and implemented well, and 9 other goals have still not been implemented. And in fact, intensive supervision is really needed. Therefore, to achieve the SDGs, reliable human resources, government policies, good synergy between stakeholders, in this case the government, companies, and the community (including educated people or academics), as well as intensive, effective, and efficient regional government supervision, are needed.